TEACHERS’ WORK MOTIVATION FROM INTRINSIC AND EXTRINSIC PERSPECTIVES ON LEARNING OUTCOMES AT ELEMENTARY SCHOOL - Imelia Sahda Salsabilla; Ruswan Ruswan; Fatah Syukur Fatah Syukur (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study aims to understand in depth the work motivation of teachers in intrinsic and extrinsic perspectives and their relation to learning performance in Andalusian Madrasas. This study uses a qualitative approach of case studies to explore teachers' real experiences, perceptions, and practices in carrying out their professional duties. The research subjects consisted of teachers in Andalusian Madrasas. Data collection was carried out through interviews, observations and documentation, and its validity was tested through triangulation of sources and data collection techniques. The results show that intrinsic motivation, such as teaching satisfaction, and commitment to students, are the dominant factors in shaping effective learning performance. Meanwhile, extrinsic motivations such as institutional support, work environment, and reward systems play a role as a reinforcer in increasing teacher enthusiasm and professionalism. The interaction between the two types of motivation forms a teacher's work behavior that is reflective, innovative, and oriented towards learning quality. This study concludes that teachers' learning performance is not only influenced by external factors, but is highly determined by the intrinsic motivational strength possessed. The implications of this research contribute to the development of qualitative-based work motivation studies and become the basis for education managers in designing strategies to improve teacher motivation and performance that are more contextual and sustainable.